Drain versus no drain in an uncomplicated elective laparoscopic cholecystectomy- an institutional study - Raju, Boyidi Venkat; Nadipenaa, Jhansi; Ganesh, Bodapudi; Pavani, Namburi; Kiran, Harshitha Usha; Nayak, Samir Ranjan (International Journal of Research in Medical Sciences, 2022)
Background: Laparoscopic cholecystectomy (LC) is the gold standard for symptomatic gallstones. Post surgery to keep a subhepatic drain is an issue of debate. A randomised trial was designed to assess the outcome of drain in elective lap cholecystectomy. Methods: A randomized control trial was done from January 2019 to June 2020 among 40 patients. They were randomised into group A: (n=20) in which subhepatic space was drained by an abdominal drain size 28F drain which was brought out through right anterior axillary port (even group) and group B: (n=20) in which there was no-drain at sub hepatic space (odd group). The end points of this study was to compare postoperative pain, fever, wound infection ,hospital stay between the two groups. Results: Mean hospital stay among drain group was 3.95±1.35 days as compared to 2.55±0.60 days among no drain group and the difference was statistically significant (p value =0.001). 8 (40%) patients with drain had port side infection as compared to 1 (5%) patient among no drain group and the observed difference was statistically significant (p value =0.02). Post operative pain abdomen assessed using VAS, and found significant 12 after surgery. The young female patients were unhappy with the drain scar and 3 cases requested for need of plastic surgery corrections also. Conclusions: The routine use of a drain in uncomplicated elective laparoscopic cholecystectomy has no benefit; in contrast, it is associated with longer hospital stay, so better to avoid the drain.